An empirical study of knowledge management system implementation in public higher learning institution - Rusli Abdullah; Mohd Hasan Selamat; Azmi Jaafar; Salfarina Abdullah; Suaini Sura (International Journal of Computer Science and Network Security (South Korea), 2008)
Without any doubt, Knowledge Management (KM) does offer the way on how to exploit intellectual capitals in business organizations. However, the KM principles can also be implemented in other types of organization such as the Higher Learning Institutions (HLI). One way to exploit KM is by implementing the KM System (KMS). As we all concern, knowledge is everywhere and how far it has been captured, collaborated and managed systematically especially in public higher learning institutions is unknown. Further more, how far KMS have been giving benefits to the students in PHLI is something that never been revealed. Besides that, the general framework of KMS, even though accepted but there are some unidentified features that has not been discovered. By adding these unidentified features, it will make the existing framework